Stabilisation of anthocyanins from spray dried hibiscus sabdariffa extracts by encapsulating in different carrier agent [electronic resource] - Zuhaili Idham, 1984- (2010)
Thesis (Sarjana Kejuruteraan (Bioproses)) - Universiti Teknologi Malaysia, 2010